Investigating Biomass Formations at Different Depths in a Slow Sand Filter - Demir, Neslihan Manav; Atci, Elif Burcu; Demir, Selami; Karadeniz, Aykut (HARD, 2018)
A laboratory-scale slow sand filtration (SSF) system was used to investigate biomass formation in different depths of SSF depending on various operating conditions in regard to filtration rate and influent iron-manganese concentrations. Results suggest that biomass formation occurs mainly in the uppermost 1.5 cm of the filter bed with slight contributions from layers between 1.5 cm and 14.5 cm. The highest volatile solids (VS) accumulation was observed in the uppermost layer as 16.93 +/- 0.07 mgVS/g dry sand, and the accumulation was found to be a function of both filtration rate and influent iron-manganese concentrations. Hydraulic conductivities were tested as a measure of biomass formation. The highest initial value of hydraulic conductivity was measured as 13.7 mu m/s, while the lowest values ranged from 3.28 to 6.62 mu m/s at the end of 55 days of operation. Hydraulic conductivities of the upper layers decreased quickly with time, while slight reductions were observed in hydraulic conductivities of the lower layers.
Keywords: slow sand filter; iron-manganese removal; biomass formation; headloss; hydraulic conductivity; DETERMINISTIC-BASED MODEL; MICROBIAL-POPULATIONS; SIMULTANEOUS REMOVAL; SECONDARY EFFLUENT; GENETIC DIVERSITY; FILTRATION; MANGANESE; IRON; PERFORMANCE; GROUNDWATER; Environmental Sciences & Ecology